The nephropathy of potassium depletion in chıldhood - Doğramacı, İhsan and Wray, Joe D. (The Turkish Journal of Pediatrics, 1963)
Two children with disorder of renal function associated with evidence of potassium depletion have been discussed. The clinical features and laboratory and renal biopsy findings in this disorder conform to those described by Relman and Schwartz in defining the nephropathy of potassium depletion as a clinical entity, and we believe that these children also showed this disorder. They are, as far as we can determine, the first children reported with this disorder. Some aspects of renal function in these children were similar to changes in renal function seen in chronic malnutrition in infancy: hyposthenuria and polyuria. But one of the definitive features - the failure of the renal tubules to respond to vasopressin stimulation, a change reversible with potassium therapy - is not present in malnourished infants. Their tubules have the capacity to respond to such stimulation. Whether the tubular disorder in this syndrome simply represents a further degree of severity is yet to be determined. Our experience with these two children leads us to suggest, as did Relman and Schwartz with regard to adults, that this entity is probably not rare in childhood and that the recognition of its occurrence will enable the clinician to provide better therapy in a variety of clinical situations.